Beyond the therapeutic orphan: children and clinical trials. Issue 2 (April 2008) - Cohen, Eyal; Shaul, Randi Zlotnik
While clinical trials have advanced the prevention and treatment of child health problems, the recruitment of children into trials still faces numerous challenges. Barriers exist at the levels of society, industry, clinicians, parents and children. Utilizing some of the lessons learned from the successful paradigm of pediatric oncology would promote collaborative networking, a culture of child-focused trial recruitment and adherence to the highest ethical standards in an effort to advance child health. As Dr Harry Shirkey said in 1968, ""Every practicing physician, especially pediatricians and pediatric surgeons, departments of pediatrics and departments of pharmacology, should closely examine their own capacities and performance in this area of greatly needed activity…… The alternative is to accept the status of ''therapeutic orphans'' for their patients.""